2005
DOI: 10.1121/1.4779284
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of psychoacoustic parameters

Abstract: Noise is defined as an audible sound which either disturbs the silence or an intentional sound listening or leads to annoyance. Thus, it is clearly defined that an assignment of noise can not be reduced to simple determining objective parameters like the A-weighted SPL. The question whether a sound is judged as noise can only be made after the transformation from the sound event into an hearing event has been accomplished. The evaluation of noise depends on the physical characteristics of the sound event, on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…The A-weighted level and the loudness are therefore not sufficient to describe sounds. This is in agreement with the results presented in [32]. A measure that is more closely related to direct human perception of noise is the loudness level [33].…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The A-weighted level and the loudness are therefore not sufficient to describe sounds. This is in agreement with the results presented in [32]. A measure that is more closely related to direct human perception of noise is the loudness level [33].…”
Section: Methodssupporting
confidence: 82%
“…This is the sound pressure level that is impinging on the ear of a resident, and thus, this level has to be judged correctly in an objective manner. Previous studies [32,36,37] have demonstrated that the sound pressure level cannot be judged as an A-weighted sound level to represent a proper hearing sensation. Therefore, an A-weighted sound level is misleading when used as an indication of subjectively perceived loudness [38,39].…”
Section: Computed R-valuesmentioning
confidence: 99%
“…Standard noise maps do not include the citizens' perception of the acoustic environment, which plays an important role in the use of the outdoor public places by citizens [68]. However, examples of soundscape mapping are available in the literature, some reporting the sound quality of the acoustic environment in terms of spatial distribution of psychoacoustic descriptors (loudness, sharpness, roughness, fluctuation strength) [69], others describing a procedure to process perceptual data and spatial information [70][71][72][73][74][75]. Two important aspects need to be addressed:…”
Section: Smartphone-based Soundscape Assessmentmentioning
confidence: 99%
“…The evaluation of noise depends on the physical characteristics of the sound, on the psychoacoustical features of the human ear and on the psychological aspects of people [5]. The main psychoacoustic parameters are the following:…”
Section: Psychoacoustics Parametersmentioning
confidence: 99%